Identifikasi dan Penguatan Lembaga Adat dalam Mendukung Pemerintahan Desa di Desa Todo Kecamatan Satar Mese Utara Kabupaten Manggarai - Stephania Wulan Olgariani; Kotan Y. Stefanus; Rafael Rape Tupen (Pusat Riset dan Inovasi Nasional, 2025)
Article 1 point 5 of Law Number 6 of 2014 defines a village as a legal community unit with the right to its origin. In its implementation, the village government may facilitate the establishment of traditional village institutions (LAD), which function to preserve customs and serve as partners in village governance. Todo Village in Manggarai Regency continues to uphold its traditional values through a functioning customary institution that plays a role as a stakeholder. However, modernization often creates tension between traditional values and modern societal demands. This research is a normative legal study supported by empirical data. The data were analyzed using a juridical-descriptive qualitative method, obtained through field research and other sources.The findings show that the traditional institution in Todo Village has adopted a more modern and administrative structure without losing its core functions in preserving local customs. It maintains a constructive partnership with the village government while each operates independently. Strengthening efforts include providing infrastructure, allocating village funds for traditional house maintenance, and establishing customary organizations to support development. However, challenges remain, especially due to the lack of specific regulations and the fact that Todo has not yet been officially designated as a customary village.